Green approach for the decoration of Pd nanoparticles on graphene nanosheets: an in situ process for the reduction of C-C double bonds and a reusable catalyst for the suzuki cross-coupling reaction - Hussain, Najrul; Borah, Ashwini; Darabdhara, Gitashree; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (New Journal of Chemistry, 2015)
A new strategy for in situ synthesis of palladium nanoparticles (Pd NPs) decorated on reduced graphene oxide (rGO) nanosheets with controlled size and shape is reported. This strategy was designed as three processes in one pot, namely, (a) reduction of graphene oxide, (b) formation of Pd NPs on the rGO nanosheets and (c) simultaneous reduction of olefin. In this synthesis process, a hydrogen atmosphere was used to develop the Pd NPs-rGO nanocatalyst, which is reusable and easily separable. The influence of the size and morphology of the Pd-rGO-H-2 catalyst on the catalytic activity in the Suzuki cross-coupling reaction was investigated by comparing with other catalysts, Pd-rGO-As and Pd-rGO-Gl, and they were synthesized by different reducing agents, ascorbic acid and glucose, respectively. The catalysts were characterized by electron microscopy (HRTEM, SEM), FT-IR, XRD and XPS. The Pd-rGO-H-2 catalyst was found to possess excellent catalytic activity and recyclability in the Suzuki cross-coupling reaction under mild reaction conditions.

Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2015)
Highly stable Cu(0) nanoparticles were synthesized on reduced graphene oxide (rGO) sheets using a cost-effective and green method. The synthesized Cu(0)-nanoparticle-rGO composites exhibit excellent catalytic activity for the synthesis of symmetrical biaryls from arylboronic acids under microwave irradiation. The reaction proceeds smoothly in base-free conditions with easy recovery and reuse of the catalyst. The methodology is compatible with various functional groups and provides an attractive protocol for the synthesis of symmetrical biaryls with very good yields. HRTEM, XPS and XRD analyses showed the catalyst to be recyclable. The Cu(0) nanoparticles are stable in the rGO nanosheets, and the particle size distribution and oxidation state of the Cu(0) nanoparticle remain the same after performing the chemical reaction.

Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions (vol 5, pg 1251, 2015) - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2016)
Correction for ‘Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions’ by Najrul Hussain et al., Catal. Sci. Technol., 2015, 5, 1251–1260.